(untitled) (Journal of Face Aesthetics, 2023)
Narrowing of the upper dental arch is one of the most common problems encountered by orthodontists in their practice. This abnormality often affects only the anterior part of the maxilla, while the lateral regions maintain the proper width. The reduced width of the dental arch results in insufficient space for the correct alignment of all teeth, leading to crowding and rotation, which significantly deteriorates the aesthetics of the smile. This paper presents a case of a patient who was found to have hypertonicity of the mental muscle during the extraoral examination, and intraoral examination revealed narrowing of the upper dental arch in the anterior segment and crowding of the upper incisors with a deficit of space for the canines. After the orthodontic diagnostic process was performed, a fan‑type expander was used as the initial treatment. With one daily activation, the desired effect of increasing the anterior maxilla width was achieved after 18 days, and a satisfactory correction of the smile was achieved after 18 months.